Histophysiological thetics on the premium bioecological level for the effecting of ultraviolet radiation of the sun in the appearance of malignant melanoma in the outdoor domestic cats at the Mesopotamia - Hassan A-S, U. (Al-Qadisiyah Journal of Pure Science, 2018)
The present study bring to light that Mesopotamia region attended an fluctuation in UV-B radiation frequency to record a range value 200-280 nm, this change in turn play a corner role in the spread a radiation environmental pollution led to the injury of the outdoor cat's integument with malignant melanoma. physiologically 10 factors were been tested to being affected by this disorder including heart beats, breathing times, ADH value, melatonin value, Ca++-K+-Na+ levels, differential WBCs (neutrophil & basophil) values, and anemia occurrence, where they were showed a change in their values considered statistically within the significance levels. On the other hand, the histopathological sections explains a type of agglutinations for some abnormal naevus cells accompanied with a shrank of the injured cells with signs of rigidity for their nucleus.Conclusion derived from the available data proved that high frequency of UV radiations at this region of Iraq causing mighty appearance of malignant melanoma at the outdoor cats.